Implementasi Manajemen Perubahan Untuk Meningkatkan Kinerjadan Daya Saing Umkm Sacio Shoes Clean - Septi, Yollanda; Laila Izzatul Rahmah; Maireza Sofia Wulandari; Abil Herlambang; Ramdhani Bayu Putra (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This research focuses on implementing change management to improve the performance and competitiveness of Sacio Shoes Clean MSMEs. This topic was chosen considering the challenges faced by MSMEs in adapting to market changes. The methods used include SWOT analysis, managerial skills training, and digital marketing strategy development. The research results showed an increase in operational performance of 30% and an increase in sales of up to 50% in six months post-implementation. Apart from that, digital marketing strategies are able to attract new consumers effectively. In conclusion, change management is the key to increasing the competitiveness of MSMEs, and the results of this research can be used as a reference for other MSMEs to adapt and develop in a competitive era.